2010
DOI: 10.3171/2010.2.jns091897
|View full text |Cite
|
Sign up to set email alerts
|

Posttreatment prognosis of patients with esthesioneuroblastoma

Abstract: A biopsy should always be obtained in cases suspected of EN because histology is a strong prognostic indicator and will help guide appropriate treatment. Unimodal surgery and combined surgery/radiotherapy appear to be of equivalent efficacy with respect to survival in patients with EN. Chemotherapy should be considered in high-grade EN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
104
1
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(119 citation statements)
references
References 189 publications
9
104
1
5
Order By: Relevance
“…6 These findings have been confirmed in a large meta-analysis published in 2010 by Kane et al 4 Further, Kane et al found, as previously published by our institution, that higher grade pathology (by Hyams criteria) may predict poorer prognosis. 4,7 This finding, however, has not been confirmed by a direct retrospective or prospectively conducted trial in a similar manner. Further, some institutions as recently as 2006 advocated no pathologic interpretation beyond confirming ENB and therefore do not report a Hyams grade, since it is believed ENB grade is of no prognostic significance.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…6 These findings have been confirmed in a large meta-analysis published in 2010 by Kane et al 4 Further, Kane et al found, as previously published by our institution, that higher grade pathology (by Hyams criteria) may predict poorer prognosis. 4,7 This finding, however, has not been confirmed by a direct retrospective or prospectively conducted trial in a similar manner. Further, some institutions as recently as 2006 advocated no pathologic interpretation beyond confirming ENB and therefore do not report a Hyams grade, since it is believed ENB grade is of no prognostic significance.…”
supporting
confidence: 76%
“…12 This series is unique in that over 75% of the ENB presented as Kadish C or D, which is substantially higher than most reported series, which typically report 50% or less. 4,9,12,15 We agree with Dulguerov et al that the current staging systems lack distinction specifically within the Kadish C cohort, such as distinguishing dural transgression; however, due to low numbers, even within this series it is difficult to firmly differentiate this subset of tumors. 2,12 However, it may be useful to divide Kadish C lesion postoperatively by whether or not negative margins could be achieved, or whether it is simply unresectable.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Other studies showed usefulness of adjuvant chemotherapy, especially in Kadish stage C high grade ONB [9]. Cisplatin-based chemotherapy, usually with etoposide, is an accepted mode of treatment in advanced, recurrent, especially high grade cases [1013], but also non-platinum schemes (irinotecan, docetaxel, doxorubicin, ifosfamide, vincristine) were described to be effective [14]. Currently no studies are available showing correlation of expression of certain proteins regarding the response to chemotherapy.…”
Section: General Informationmentioning
confidence: 99%
“…Chemotherapy can be used in an adjuvant or neoadjuvant attempt and also in the metastatic phase or recurrent or advanced disease, although its effectiveness has still not been established. Such multimodality therapy has become the most common approach to esthesioneuroblastoma [13] [14].…”
Section: Discussionmentioning
confidence: 99%